PUBLIC PERCEPTION IN THE MANAGEMENT OF INTEGRATED ISLAMIC ELEMENTARY SCHOOLS IN TOJO UNA-UNA REGENCY - Harma D. Mahmud; Sitti Roskina Mas; Nina Lamatenggo (Adisam Publisher, 2025)
This research aims to describe; (1) What is the community's perception of the implementation of curriculum management (2) What is the community's perception of the implementation of school and community relations management at SD IT AL- Wahdah Tojo Una-Una. This research uses mixed research methods with an exploratory type of research. Data collection techniques through observation, distribution of questionnaires, interviews and documentation studies. The data analysis process was carried out using descriptive percentage analysis techniques. The research results show that: (1) community perception of curriculum implementation at SD IT Al-Wahdah Tojo Una-Una with a percentage of 85.85% is in the good category. This can be seen in the implementation of curriculum management functions in planning, implementation and also the evaluation process. By combining the national curriculum and the Wahdah Islamiyah curriculum, this school is much sought after by the public. (2) Community perception of the implementation of school and community relations management at SD IT Al-Wahdah Tojo Una-Una with a percentage of 88.17% is in the good category. This can be seen in the planning, implementation and evaluation of the management of school and community relations which has been carried out well, so that through these public relations activities SD IT Al-Wahdah Tojo Una-Una is increasingly known to the community.